2014
DOI: 10.1186/1472-6963-14-50
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hospital mergers on long-term sickness absence among hospital employees: a fixed effects multivariate regression analysis using panel data

Abstract: BackgroundHospitals are merging to become more cost-effective. Mergers are often complex and difficult processes with variable outcomes. The aim of this study was to analyze the effect of mergers on long-term sickness absence among hospital employees.MethodsLong-term sickness absence was analyzed among hospital employees (N = 107 209) in 57 hospitals involved in 23 mergers in Norway between 2000 and 2009. Variation in long-term sickness absence was explained through a fixed effects multivariate regression anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
42
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 47 publications
3
42
2
Order By: Relevance
“…Studying the same hospital mergers as those analyzed in this article, Kjekshus et al (2014) found that sickness absence among staff who remained employed at the same hospital was significantly higher in the merger year and in the second to fourth year after the merger than in nonmerger years. Josephson et al (2008) argue that turnover and sickness absence are two separate ways of actively coping with unhealthy working conditions.…”
Section: Mergers Health and Turnovermentioning
confidence: 77%
See 4 more Smart Citations
“…Studying the same hospital mergers as those analyzed in this article, Kjekshus et al (2014) found that sickness absence among staff who remained employed at the same hospital was significantly higher in the merger year and in the second to fourth year after the merger than in nonmerger years. Josephson et al (2008) argue that turnover and sickness absence are two separate ways of actively coping with unhealthy working conditions.…”
Section: Mergers Health and Turnovermentioning
confidence: 77%
“…Employee participation is generally believed to facilitate restructuring at the company level (Løken et al, 2013). When studying the effects of hospital mergers in Norway on the employees, it is important to keep in mind that the hospital mergers in Norway have not entailed major downsizing (Kjekshus et al, 2014).…”
Section: Hospital Mergers In Norwaymentioning
confidence: 99%
See 3 more Smart Citations